IMPLEMENTASI KEBIJAKAN BANTUAN BEDAH RUMAH KECAMATAN KUOK KABUPATEN KAMPAR TAHUN 2022 - ', Mutiara; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Home surgery assistance is a public policy implemented by the Kampar Regency government to solve housing problems faced by the community, especially in rural areas. However, this policy has different goals, objectives, mechanisms, and impacts. There are still many people in Kuok District, especially the people of Kuok Village and Jambu Island Village, who do not know about the existence of house surgery assistance even though this assistance has been running since 2017. Many of the recipients of home surgery assistance are not on target so that people with low economies do not get the assistance as they should. The purpose of this study is to find out how the implementation of the house surgery policy in Kuok District, Kampar Regency in 2022. This research was conducted in Kuok Village and Jambu Island Village, Kuok District and the Kampar Regency Public Housing and Settlement Area Office. This study uses a qualitative research method with a descriptive approach and in data collection the researcher uses interview and documentation techniques as well as data analysis techniques for data reduction, data presentation, and conclusion drawn. Based on the results of research on the implementation of the house surgery policy in Kuok District, Kampar Regency in 2022 by the Kampar Regency Public Housing and Settlement Areas Office for the implementation of house surgery assistance in Jambu Island Village and Kuok Village, Kuok District has been going well. However, it also needs to be improved again and it is better that the Public Housing and Settlement Areas Office needs to socialize it directly to the community so that information related to this house surgery assistance is conveyed to the community optimally. Keywords: Implementation, Policy, Home Surgery